A Rationale, or practical exposition of the Book of common-prayer - Sparrow, Anthony (Printed by J. Bettenham, for Charles Rivington, 1722)
Lives of the compilers, includes: Thomas Cranmer, Nicholas Ridley, Thomas Goodrich, Henry Holbech, John Skip, Thomas Thirlby, George Day, John Taylor, Richard Cox, William May, Thomas Robertson, Simon Heynes, and John Redmayne.